The impact of the transformation and merger of the one-person company with limited liability on her legal personality - Abdallah Hameed Al Ghuwairi ,; Abdulwahab Abdullah , (Technium Social Sciences Journal, 2020)
This study discussed the legal texts that treat the conversion and merger of one-person limited liability company, which is considered as a type of limited liability company and subject to its provisions. Jordanian law regulates the provisions relating to the conversion of the company in articles, the law defines the form in which a limited liability company may be referred to in article, “a public shareholding company”. The study discussed the definition of the transfer of the company, the required conditions and the procedures and effects of the transfer to the others and creditors, and also dealt with articles which relating of merger provisions, and the concept of merge was defined, the conditions and methods in which it is carried out and its procedures and the objection there to has been identified as challenging its invalidity and the legal effects that it entails. The researcher followed the descriptive method and analyzed and compared texts dealing with the conversion and merger of the one-person company with limited liability. The study focused on the impact of conversion and merger on the legal personality of the company. The study was divided into two sections, and each section was divided into three demands, and concluded the study by presenting a set of recommendations.